Reforming government policies on flexible working arrangements (FWSs) for the attainment of national sustainable development goals (SDGs) - Sharifah Rahama Amirul; Sharija Che Shaari; Khairul Hanim Pazim (Zes Rokman Resources, 2021)
This working paper calls for reforming laws and policies on flexible working arrangements (FWAs), which can play as a critical enabler to support the national sustainable development goals since it has impacted good health and well-being, gender equality, as well as decent work and economic growth. Our proposed FWAs policy framework emphasises the importance of elderly workers, the women participation rate in the workforce, the harmonious work-life balance of working parents, and the broad scope is for national productivity and economic growth. Based on the report issued by the Department of Statistics of Malaysia in 2019, it was anticipated that Malaysia would be an ageing nation by 2030. The clock is ticking down, Malaysia will have less than a decade to prepare for the incoming wave of ageing population. When we take a closer look at countries that have had or are experiencing an ageing population, they are mostly facing rising healthcare and pension costs, and a shrinking workforce. By reforming FWAs policies for elderly workers, it provides opportunities for them to work for a longer period of time, accumulate larger superannuation earnings and are less dependent on the government pension throughout their retirement years. Employees also contribute to a rise in tax revenue. There are also considerable associations between engagement in the labour force and overall health status. Working appears to be a protective factor against physical ill-health and poor mental health. With the proper FWAs policy framework in place, it will encourage gender equality in the workplace by encouraging the participation rate of women in Malaysia. Meanwhile it also becomes a remedy to the dilemma of work-life conflict among working parents. FWAs are also deemed to be important to cater to the social needs of millennial employees in today’s modern life. FWAs are also becoming increasingly important in order for organisations to adapt with global economy evolution and the current pandemic has accelerated the demand and implementation of FWAs even further. Conventionally, governments’ effort in supporting FWAs has been associated with the formation of Acts and regulations related to FWAs, especially in developed countries such as the UK, Australia, and New Zealand. Through regulation, these governments have covered the rights of employees to request FWAs, limiting employees’ rights to challenge their employer and other FWA-related matters. As a developing country, it is the right time for our country to take a further step toward achieving support the national sustainable development goals. Our FWAs policy’s framework is expected to stimulate progressive workplaces, and retain talent, ultimately improving overall productivity and boost our national economic growth.